Private rare deletions in SEC16A and MAMDC4 may represent novel pathogenic variants in familial axial spondyloarthritis. Issue 4 (8th May 2015) - O'Rielly, Darren D; Uddin, Mohammed; Codner, Dianne; Hayley, Michael; Zhou, Jiayi; Pena-Castillo, Lourdes; Mostafa, Ahmed A; Hasan, S M Mahmudul; Liu, William; Haroon, Nigil; Inman, Robert; Rahman, Proton
Abstract : Objective: Axial spondyloarthritis (AxSpA) represents a group of inflammatory axial diseases that share common clinical and histopathological manifestations. Ankylosing spondylitis (AS) is the best characterised subset of AxSpA, and its genetic basis has been extensively investigated. Given that genome-wide association studies account for only 25% of AS heritability, the objective of this study was to discover rare, highly penetrant genetic variants in AxSpA pathogenesis using a well-characterised, multigenerational family. Methods: HLA-B*27 genotyping and exome sequencing was performed on DNA collected from available family members. Variant frequency was assessed by mining publically available datasets and using fragment analysis of unrelated AxSpA cases and unaffected controls. Gene expression was performed by qPCR, and protein expression was assessed by western blot analysis and immunofluorescence microscopy using patient-derived B-cell lines. Circular dichroism spectroscopy was performed to assess the impact of discovered variants on secondary structure. Results: This is the first report identifying two rare private familial variants in a multigenerational AxSpA family, an in-frame SEC16A deletion and an out-of-frame MAMDC4 deletion. Evidence suggests the causative mechanism for SEC16A appears to be a conformational change induced by deletion of three highly conserved amino acids from the intrinsically disordered Sec16A N-terminus and RNA-mediated decay for MAMDC4 . Conclusions: The results suggest that it is the presence of rare syntenic SEC16A and MAMDC4 deletions that increases susceptibility to AxSpA in family members who carry the HLA-B*27 allele.